Advocacy of Precision Allergy Molecular Diagnosis in Decision Making for the Eligibility of Customized Allergen Immunotherapy - González-Pérez, Ruperto; Poza-Guedes, Paloma; Pineda, Fernando; Sánchez-Machín, Inmaculada (Current Issues in Molecular Biology, 2023)
Allergen immunotherapy (AIT) with aeroallergens is the only disease-modifying treatment for patients with different allergic conditions. Despite the effectiveness of AIT having been proven in both randomized controlled trials and real-world studies, it remains underused in less than 10% of subjects with allergic rhinitis (AR) and/or asthma (A). We aimed to determine the current eligibility for house dust mite (HDM) AIT by means of a precision allergy molecular diagnosis (PAMD@) model in a selected cohort of youngsters with different allergic phenotypes according to the available evidence. A complex response to both HDM and storage mite allergens was depicted regardless of the subjects’ basal atopic condition. No solely specific IgE-binding responses to Der p 1, Der p 2, and/or Der p 23 were found in the studied cohort. Despite the patients with A and atopic dermatitis showing significantly higher serum titers to six mite allergens than subjects with AR, no specific molecular profile was regarded as disease specific. Given the increasing complexity of specific IgE responses to the local prevailing aeroallergens, the identification and presence of such molecules are needed in commercially available AIT in the era of precision medicine.